2014
DOI: 10.1111/are.12382
|View full text |Cite
|
Sign up to set email alerts
|

Changes of heritability and genetic correlations in production traits over time in red abalone (Haliotis rufescens) under culture

Abstract: Red abalone Haliotis rufescens is one of the most valuable mollusks in the international market, but it has a low growth rate. A breeding program is being developed to increase its growth rate in Chile. We estimated the changes in direct heritability (h2), maternal/common environments heritability (m2) and genetic correlations (rG) of growth traits (shell length and width, total mass, flesh mass and foot protein as an indicator of meat quality) measured during 2 years (every 4 months) from the juvenile stage (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…, Brokordt et al. ), highlighting the importance of estimating heritability through different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Brokordt et al. ), highlighting the importance of estimating heritability through different developmental stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known how these results for the early life-cycle stages translate to macroscopic adults. However, in abalone and other shellfish, heritabilities of growth traits become stronger as the organism ages while phenotypic expression due to maternal and environmental effects are more pronounced in juveniles (Coman et al 2010, Brokordt et al 2015, highlighting the importance of estimating heritability through different developmental stages. Tests of significance: *P < 0.05; **P < 0.01; ***P < 0.001.…”
mentioning
confidence: 99%
“…Numerous studies have shown that growth is a heritable trait in Haliotis spp. (Lucas et al 2006, Robinson et al 2013, Roussel et al 2013, Camara & Symonds 2014, Brokordt et al 2015, although the estimation of heritability varies widely among species and for the same species. Neverthe-less, improved growth of the F 1 generation is not always observed in spite of the fact that growth in weight is a heritable trait.…”
Section: Discussionmentioning
confidence: 99%
“…1), which grows quickly and reaches a large size in culture; popular in the US market, they are also one of the most valuable species in the mollusc industry (Aguilar-Espinoza et al. 2014; Brokordt et al. 2015).…”
Section: Introductionmentioning
confidence: 99%